The Influence of Globalization on Social Change in Simpang Baru District of Pekanbaru City - Lubis, Aisyah; Tiurmauli, Gracia; Istigfaroh, Halila; Sakinah, Hayati; Tulhusna, Izzah; Syafitri, Kirana; Mustika, Lodia; Aini, Maisya Ratul; Haryono, Haryono (Journal of English Language and Education, 2026)
Globalization has brought significant and multidimensional changes to the social life of the people of Simpang Baru Village, Binawidya District, Pekanbaru City, influencing patterns of behavior, interaction, and values through the rapid flow of information, technology, and global culture. This study aims to describe and analyze the impact of globalization on technology use, economic activities, cultural practices, and social interaction within the local community by employing a descriptive qualitative approach. Data were collected through observations, in-depth interviews, and documentation involving community members and local stakeholders to obtain a comprehensive understanding of the phenomenon. The findings indicate that globalization has generated positive impacts, particularly in the technological aspect, where easier access to information and communication technologies has improved efficiency in daily activities and expanded community knowledge. Economically, globalization has opened new opportunities through digital platforms, small businesses, and access to broader markets, contributing to improved livelihoods and economic growth. In terms of lifestyle, the community has increasingly adopted modern ways of living characterized by practicality and global connectivity. However, the study also reveals several challenges arising from globalization, including weakened face-to-face social interaction as digital communication becomes more dominant, a gradual decline in local cultural values and traditions, especially among younger generations, and increased dependence on technology that reduces social sensitivity and communal solidarity. In conclusion, globalization presents both opportunities and challenges for the social life of the Simpang Baru community; therefore, it needs to be managed wisely so that its benefits can be maximized without neglecting local cultural identity and the preservation of social cohesion.